Paradigm Shift in Language Teaching and Language Teacher Education - Borges, Elaine Ferreira do Vale (The ESPecialist, 2014)
In this article, I intend to conduct a short literature review and discussion about paradigm shift in language teaching and language teacher education from Cartesian to the complexity paradigm. For that, I use the Kuhnian notion of scientific revolution to present a short compilation of works related to paradigm shift in different sciences, including psychology, linguistics and, more emphatically, applied linguistics. The main proposal is to show the evolutions of paradigm shift in language and social sciences and its impact on the emergence of the complexity paradigm in language teaching and language teacher education fields.